Wideband (15–260 kHz) acoustic volume backscattering spectra of Northern krill (Meganyctiphanes norvegica) and butterfish (Peprilus triacanthus). (28th August 2017) - Jech, J. Michael; Lawson, Gareth L.; Lavery, Andone C.
Abstract: Measurements of acoustic backscatter made over a wide frequency band have the potential for improved classification relative to traditional narrowband methods, by characterizing more fully the frequency response of scatterers. In January 2014, five wideband transceivers [Simrad EK80 Wideband Transceivers (WBTs)] and split-beam transducers with nominal centre frequencies of 18, 38, 70, 120, and 200 kHz were used to collect acoustic data spanning a nearly continuous 15–260 kHz bandwidth. The acoustic samples were from ca. 2 m below the surface to the seabed in an area along the US continental shelf break. Bottom trawls and zooplankton nets were also used to sample scatterers contributing to selected features of the acoustic backscatter. Measurements of frequency-dependent volume backscattering strength (i.e. volume backscattering spectra) from aggregations of euphausiids (mostly Northern krill, Meganyctiphanes norvegica ) clearly resolved the transition from Rayleigh to geometric scattering, consistent with modelled backscatter from the type and length of animals sampled with bongo nets. Volume backscattering spectra from aggregations dominated by butterfish ( Peprilus triacanthus ) revealed a frequency response that was suggestive of superimposed scattering by soft tissue and bone. Backscatter predicted by Kirchhoff ray mode models of butterfish corresponded to trends in the measured spectra, supporting the assumption that acoustic scattering by butterfish is dominated by soft tissue and vertebrae.